Effects and Mechanisms by Which Hypercapnic Acidosis Inhibits Sepsis-Induced Canonical Nuclear Factor-κB Signaling in the Lung. Issue 4 (April 2016) - Masterson, Claire; O'Toole, Daniel; Leo, Annemarie; McHale, Patricia; Horie, Shahd; Devaney, James; Laffey, John G.
Abstract : Objective: Diverse effects of hypercapnic acidosis are mediated via inhibition of nuclear factor-κB, a pivotal transcription factor, in the setting of injury, inflammation, and repair, but the underlying mechanisms of action of hypercapnic acidosis on this pathway is unclear. We aim to examine the effect of hypercapnic acidosis on the nuclear factor-κB pathway in the setting of Escherichia coli– induced lung injury and characterize the underlying mechanisms in subsequent in vitro studies. Design: In vivo animal study and subsequent in vitro studies. Setting: University Research Laboratory. Subjects: Adult male Sprague-Dawley rats and pulmonary epithelial cells. Interventions: Following pulmonary IκBα-SuperRepressor transgene overexpression or sham and intratracheal E. coli inoculation, rats underwent 4 hours of mechanical ventilation under normocapnia or hypercapnic acidosis, and nuclear factor-κB activation, animal survival, lung injury, and cytokine profile were assessed. Subsequent in vitro studies examined the effect of hypercapnic acidosis on specific nuclear factor-κB canonical pathway kinases via overexpression of these components and in vitro kinase activity assays. The effect of hypercapnic acidosis on the p50/p65 nuclear factor-κB heterodimer was then assessed. Measurements and Main Results: Hypercapnic acidosis and IκBα-SuperRepressor transgene overexpression reduced E. coli– induced lung inflammation and injury, decreased nuclear factor-κB activity, and increased animal survival. Hypercapnic acidosis inhibited canonical nuclear factor-κB signaling via reduced phosphorylative activation, reducing IκB kinase-β activation and intrinsic activity, thereby decreasing IκBα degradation, and subsequent nuclear factor-κB translocation. Hypercapnic acidosis also directly reduced DNA binding of the nuclear factor-κB p65 subunit, although this effect was less marked. Conclusions: Hypercapnic acidosis reduced E. coli inflammation and lung injury in vivo and reduced nuclear factor-κB activation predominantly by inhibiting the activation and intrinsic activity of IκB kinase-β. Abstract : Supplemental Digital Content is available in the text.